A Bridge through Time: The Epistolary Form and Nonlinear Temporality in Stephen Graham Jones’s Ledfeather - Perdieu, Zachary (Transmotion, 2023)
This article explores how Stephen Graham Jones adapts the epistolary form in his novel Ledfeather to create a new textual space capable of depicting nonlinear, spatialized time. Jones’s evolution of the epistolary mode creates a two-way temporal bridge within his narrative where past, present, and future can interact. This experimentation with the epistolary form acts as a rumination on the limits of a western, linear understanding of time when coping with historical and ancestral trauma. His subsequent deconstruction of the epistolary form then mirrors the collapse of the novel’s two independent timelines as they conflate to become a single, interactive and cohabitated temporality that spans generations. As the novel progresses, the barriers between the two primary narrative timelines of Doby Saxon and Indian Agent Francis Dalimpere began to wane, and this fracturing of time is mirrored by each narratives’ respective forms slowly collapsing, as well, until the Dalimpere sections become less epistolary, and Saxon’s sections increasingly take on formulaic standards of the epistolary mode. By collapsing the two timelines and merging the respective forms of each section, Jones introduces a new hybridized textual space which speaks to a nonlinear conception of temporality, giving space primacy over time in mapping history, memory, and narrative.